Business and Security Sector Reform The Case for Corporate Security Responsibility - Rosa Mendes, Pedro (SSR Papers, 2015)
Challenges to security and human rights involving extractive and other industries are addressed in a framework known as business and human rights (BHR), which shares many challenges and goals with SSR. This paper describes the grounds where BHR and SSR coincide in principles, actors and activities and which synergies can be built on that base. Opportunities for bridging BHR and SSR are drawn from a systematic comparison of case studies on Guinea, Colombia and Papua New Guinea. BHR and SSR should ideally cohere instead of collide.